Profile of Ophthalmic Tumors in Adult Nepalese Population in Central Nepal - Pant, Nayana; Shrestha, Gulshan Bahadur; Joshi, Sagun Narayan; Bhatta, Subash (Nepalese Journal of Ophthalmology, 2020)
Introduction: Ophthalmic tumors cover benign and malignant tumors of eyelids, conjunctiva, globe, and orbit. There is limited literature on ophthalmic tumors in Nepal. The objective of the study was to find the relative frequency of various ophthalmic tumors in the adult Nepalese population in Central Nepal. Material and methods: This is an observational descriptive study. A total of 100 consecutive patients, presenting with ophthalmic tumors to tertiary referral eye hospital were enrolled for the study. Demographic profile, detailed history, clinical features and diagnosis of the ophthalmic tumors were recorded. The tissue from incisional or excisional biopsy was then subjected to histopathological examination for confirmatory diagnosis. Results: Mean age of subjects with ophthalmic tumors was 51.5 ± 18.2 years with a female to male ratio of 1.2:1. Benign tumors (64%) were the most common tumors followed by malignant (26%) and premalignant tumors (10%). Most common benign tumor was naevus (26.5%); most common premalignant tumor was conjunctival intraepithelial neoplasia (60%), and most common malignant tumor was sebaceous gland carcinoma (30.8%). Eyelid was most frequently involved with ophthalmic tumors (59%) followed by conjunctiva (21%). Clinical diagnosis correlated with histopathological diagnosis in 77% of cases. Conclusion: As different ophthalmic tumors present in a myriad of ways and a significant proportion of these cases presenting to hospital settings are malignant, it is prudent to confirm with a histopathological diagnosis for optimum management of such cases.